Efficiency and optimization of building insulation with the help of facade systems - Savenko, V.; Dubynka, O.; Orishchenko, V.; Polosenko, O.; Tugai, A. (Ways to Improve Construction Efficiency, 2022)
In the article Selection of optimal technological solutions for the installation of hinged ventilated facades using calculations. Necessary factors are identified, in which the optimal methods of facade insulation, the minimum period of time for installation work and the corresponding cost of materials and works are determined. Optimization of organizational and technological solutions can be achieved due to the limit limitations of design indicators. The solution of this task was carried out using the combination of duration and cost diagrams. Minimization of resource costs can be achieved by increasing the number of work teams and working days per week. According to the results of the research, the following parameters of the technological process were recommended for the use of the following parameters of the technological process, provided that the minimum indicators of cost and duration were achieved when installing single-layer thermal insulation systems: - number of crews - 3; - number of working days per week - 6. The construction duration indicator is one of the most important at all stages of organizational, design and economic preparation for the installation of the house insulation system. The duration of warming is determined according to the calendar schedule. In turn, the cost of construction and installation work may change during the construction process due to changes in the cost of the project as a whole. Therefore, it is also quite relevant to determine the influence of organizational and technological factors on it.